Online purchasing: Malaysian customers awareness factors / Muhammad Taufik Salleh - Salleh, Muhammad Taufik (2009)
While an increasing number of customers in Malaysia frequently shop on the internet, research on what drives customers to shop online has typically been fragmented. This paper therefore proposes a framework about the understanding of customers awareness factor on online purchasing. The review shows that customer's awareness on online shopping are not only affected by web design and internet security, but also by information on the internet and internet trustworthy. The purpose of this study is to look into the current situation of customer awareness on online purchasing in Malaysia as the impetus in meeting the efforts towards larger internet marketplaces such as eBay and Amazon.com.